Avoiding the trap: the dynamic interaction of North-South capital mobility and technology diffusion - Michael Hübler (Kiel Institute for the World Economy (IfW), 2009)
This paper analyzes a stylized model of international capital mobility and diffusion of embodied technologies from North to South. The South can fall behind in terms of technologies or get trapped in a situation, in which it is unable to attract foreign capital and embodied technologies, if its absorptive capacity is too low. The paper reconciles the view that technological catching up is stronger, the larger the technology gap with the alternative view that technological catching up is strongest at a medium technology gap. The closer the South is to the technology frontier, the more beneficial is a higher income share of foreign capital. The speed of technology diffusion is higher in small economic regions with high population densities.
Keywords: F21; O11; O33; O47; 330; Technology diffusion; technology transfer; capital mobility; human capital; absorptive capacity; Internationale Kapitalmobilität; Technologietransfer; Innovationsdiffusion; Nord-Süd-Beziehungen; Entwicklungskonvergenz; Direktinvestition; Theorie